Gum arabic: determination of solvent effect on the extraction of phenolic compounds and antioxidant activity using principle component analysis - Mohamed Elnour, Ahmed Adam; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Musa, Khalid Hamid (2018)
This study is on Gum Arabic (GA), which is a plant exudate from Hashab (Acacia senegal) tree. It provides a rich source of non-viscous soluble fiber that is used traditionally in folk medicine. The challenge and aim of this research are the selecting appropriate solvent for extraction of antioxidants from Hashab Gum Arabic (HGA). Solid- liquid solvents extraction (SLSE) is one of the most effective techniques for the recovery of antioxidant and phenolic compounds from HGA. This study investigates the effect of the solvent on the extraction of total phenolic content (TPC) and antioxidant activity from HGA using pure solvents (distilled water, methanol, ethanol and acetone) and their aqueous mixtures at 50% and 100% respectively, within two different locations clay and lateritic soils. The capacity of the extracts was determined by the scavenging activity of 1,1-diphenyl-2- picrylhydrazyl (DPPH+•) radical, ferric reducing antioxidant power (FRAP) assay, and Folin-Ciocalteu Index (FCI) assay for TPC. The results indicated that the 100% methanol was more efficient solvent in the extracting of phenolic compounds, and get the highest antioxidant capacities. Moreover, HGA presented the highest antioxidant capacities and total phenolic content compared to other samples from Acacia spp. The coefficient of determination (R2) indicated that there is a significant (P≤0.05) correlation between TPC and FRAP, and CUPRAC respectively, however, there is no correlation between TPC and DPPH in terms of different location clay and lateritic soil. HGA extract is rich in polyphenolic compounds which are extremely affected by the solvent combinations used. In addition, the obtained extracts using pure methanol was distinguished from the extracts obtained with mixtures of organic solvents, through the multivariate analysis using PCA and HCA analyses. Based on these findings, it is concluded that Acacia senegal gum (HGA) constitutes a natural source of potent antioxidants that may prevent many diseases and could be potentially used in food, cosmetics, and pharmaceutical products.